(untitled) (Sudurpaschim Spectrum, 2024)
This research investigates the ways in which copyright legislation adjusts to emerging technologies, with a particular emphasis on digital progress and artificial intelligence (AI). It underscores the challenges posed by AI and digital platforms to conventional copyright principles, notably in terms of authorship and ownership. The study also evaluates Nepal’s Copyright Act of 2002, pinpointing shortcomings in its capacity to address concerns such as online piracy and content created by AI. Through a legal comparative method, this research contrasts Nepal’s regulations with international frameworks, including the Berne Convention and WIPO treaties. It highlights the lack of specific clauses regarding works generated by AI and digital formats in Nepal’s legislation, even though it aligns with global standards in various other respects. The results indicate that existing copyright laws are insufficient for regulating works produced by AI. Such creations often have ambiguous authorship and ownership because of the non-human aspect of AI. Various countries approach these matters differently, leading to global discrepancies. Nepal’s ability to enforce copyright faces challenges due to limited resources and outdated systems, making it difficult for creators to protect themselves from infringement. To tackle these issues, the study recommends that Nepal revise its copyright law to encompass AI-generated content, implement more rigorous strategies against online piracy, and align with international best practices. Suggested measures include clearly defining authorship for works produced by AI, bolstering enforcement practices, and enhancing public understanding. Making these adjustments would safeguard creators while promoting innovation and knowledge accessibility. In summary, updating Nepal’s copyright legislation to address challenges posed by AI and digital technology is crucial for protecting creators’ rights, fostering innovation, and improving competitiveness on a global scale.